166k views
24 votes
Solve the equation by completing the square. x²+6x-4=0​

User Bigsby
by
4.8k points

1 Answer

10 votes

Answer:

x = √13 - 3

x = -√13 - 3

Explanation:

Given :

  • x² + 6x - 4 = 0

Solving :

  • x² + 6x + 9 - 9 - 4 = 0 [Adding and subtracting 9]
  • (x + 3)² - 13 = 0 [Group the square term together]
  • (x + 3)² -13 + 13 = 0 + 13 [Add 13 on both sides]
  • √(x + 3)² = √13 [Taking square root on both sides]
  • x + 3 - 3 = ±√13 - 3 [Subtract 3 from both sides]
  • x = ±√13 - 3

Solutions :

  1. x = √13 - 3
  2. x = -√13 - 3
User Ana Koridze
by
5.2k points